Effect of preshipment preconditioning and injectable antioxidant trace elements (Cu, Mn, Se, Zn) and vitamins (A, E) on plasma metabolite and hormone concentrations and growth in weaned beef cattle - Galarza, Esteban Martín (2021)
Weaning and transport represent a high stress time for calves. Preconditioning (PC) by weaning before the transport separate these stressors. The stressors generate oxidative stress, which can be reduced by mineral and vitamin supplementation (MVS) with an antioxidant capacity. Our objective was to evaluate the effect of PC and MVS on performance of steers. The experiment used a 2 × 2 factorial arrangement design, considering a 26-d PC treatment from weaning to transport to the feedlot (day 0), and injectable MVS on days -45, -26, and 0. The MVS consisted of Cu, Zn, Mn, Se, vitamin E (0.2, 0.8, 0.2, 0.1, and 1 mg/kg body weight [BW], respectively), and vitamin A (1,190 IU/kg). Sixty Angus-crossbred steers (186.4 ± 27.6 kg) were randomly assigned to the four treatments (MVS+PC; N+PC; MVS+N; N+N; n = 15 per treatment). BW was recorded on days -45, -26, 0, 8, 15, and 29. On day 0, an additional BW was taken 30 min after the 5-h transportation (day 0.5). Between days 0 and 29, dry matter intake (DMI) and average daily gain (ADG) to DMI ratio (G:F) were measured. Between days -26 and 29 plasma concentrations of glucose, nonesterified fatty acids (NEFA), cortisol, insulin, total antioxidant status (TAS), and thiobarbituric acid-reactive substances were evaluated. Data were analyzed using the MIXED procedure of SAS with repeated measures, using treatment, time, and treatment × time as fixed effects and steer as a random effect. Between days -26 and 0, there was an interaction of MVS × PC (P ˂ 0.01) for ADG. From days -26 to 0, N+N and N+PC had the greatest and lesser ADG, respectively. On day 0.5, no-PC steers tended to lose BW, whereas the PC steers tended to gain BW (P = 0.09). In the period days 0 to 8, there were no differences (P ≥ 0.27) in DMI, but the PC steers had greater G:F and ADG (P < 0.01) compared with no-PC steers. Plasma NEFA concentration on day 0 was affected by MVS × PC (P < 0.01) because MVS decreased plasma NEFA concentration in no-PC steers, but it increased in the PC steers. Plasma concentrations of glucose, insulin, and cortisol did not differ among treatments (P ≥ 0.23). There was an MVS × PC interaction (P = 0.09) for TAS on day 0; N+N had the greatest TAS concentrations and MVS+N had the lowest TAS concentrations. In conclusion, a 26-d PC decreased steers BW compared with no-PC steers. The BW loss during PC was not recovered 29 d after feedlot entry. Despite this BW loss, MVS treatment decreased BW loss in the steers allocated to PC treatment on the day of transport.